Діагностичне та прогностичне значення інтегральної оцінки динаміки біоелектричної активності головного мозку в гострий період мозкового ішемічного супратенторіального інсульту - Кузнєцов, Антон Анатолійович; Kuznietsov, A. A. (My University, 2013)
The results of computed electroencephalography investigations of 120 patients in dynamics of acute period of ischemic supratentorial stroke are presented in this article. The peculiarities of brain’s functional reorganization in patients in acute period of ischemic supratentorial stroke on the basis of clinical electroencephalographic comparisons were revealed. Neurophysiological mechanisms of different clinical social outcome realization of the stroke's acute period are described. Informative electroencephalographic criteria of disease severity estimation and stroke’s acute period prognosis in indicated cohort were proposed.
Diagnostic and Prognostic Value of Bioelectrical Brain Activity Integral Estimation in Acute Period of Ischemic Supratentorial Stroke
Keywords: ишемічний інсульт; електроенцефалографічний патерн; прогноз; ischemic stroke; electroencephalographic pattern; prognosis